Comparison of oncological, surgical, and functional outcomes between radical retropubic and radical perineal prostatectomy: A multi-institutional study. Issue 1 (February 2023) - Moussa, Mohamad; Abou Chakra, Mohamad; Peyromaure, Michael; Barry Delongchamps, Nicolas; Bailly, Hugo; Duquesne, Igor
Introduction: To investigate the safety, oncologic, surgical, and functional outcomes of RPP and RRP for localized prostate cancer (Pca), especially focusing on RPP. Materials and methods: From March 2005 to January 2021, we retrospectively reviewed the records of 685 patients undergoing RPP ( n  = 320) or RRP ( n  = 365) for localized Pca. Surgical and functional outcomes, and complications were compared. Oncological outcomes were also compared using Kaplan-Meier survival analysis. Results: A higher biochemical recurrence rate were noted in RRP than in RPP group (28.8% vs 21.6%, respectively; p  = 0.03). A local recurrence was detected in a few numbers of patients (4.4%) with no statistically significant differences by surgical groups ( p  = 0.71). No significant differences were observed in the cancer-specific survival and the overall survival according to the surgical approach. Positive surgical margins were similar in the two techniques. In comparison to RRP, patients undergoing RPP have less postoperative pain, decreased transfusion rate, and less catheterization time. Complete continence was achieved in 96.9% of the RPP group at 18 and 24 months versus 91.8% and 92.3% in the RRP group at 18 and 24 months, respectively ( p  = 0.005 and p  = 0.01, respectively). At 18 months of follow-up, the nerve-sparing technique was performed equally between the two groups, the mean of erectile function domain improved more in RPP than RRP (12.71 vs 10.42 respectively, p  < 0.001). Medical and surgical complication rates were higher for RRP than RPP. Conclusions: RPP showed acceptable oncologic outcomes and excellent functional outcomes when compared to RRP.